Directive Speech Acts of Public Figures in Shaping the Character of the Nation’s Youth Towards a High-Quality Indonesia - Amalia, Nur Rafika; Prayitno, Harun Joko (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the types of directive speech acts used by public figures such as Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo and examine their influence on the character formation of the young generation of Indonesia. These three figures often use social media as a means of public communication that is full of persuasive messages through speech acts in the form of invitations, commands, advice, suggestions, and prohibitions. This study uses a qualitative approach with a descriptive method and data collection techniques in the form of document research from various online media sources such as Twitter, Instagram, Facebook, and Youtube. The results of the study indicate that character can improve the integrity, nationalism, and competence of the young generation through various types of command language acts such as invitations, commands, suggestions, advice, and prohibitions that shape personality. These speech acts have a major influence on the development of critical thinking, responsible attitudes and active participation in national development. This study concludes that the role of public figures using innovative speech acts is very important in the formation of the character of the young generation who are ready to face future challenges and build a quality Indonesia.